Children with mental disorder and the law [electronic resource] : a guide to law and practice - Harbour, Anthony (Jessica Kingsley Publishers, 2008)
Children and young people with complex mental health needs are increasingly being cared for within specialist mental health care settings, either in the community or in in-patient facilities. With rapid social developments, it can be difficult for carers and practitioners to keep track of the law in this area. This book provides a guide to the law relating to mental health care for children and young people, their rights and entitlement to service, and discusses important issues in clinical and social care practice such as parental responsibility, Gillick competency and capacity, emergency int.